(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to develop a straight and cross smash drill training model using root obstacles to improve smash accuracy in extracurricular volleyball students. This study uses the Research and Development (R&D) method with a development model referring to the Borg & Gall 7-step model, namely: (1) Preliminary study, (2) Planning, (3) Initial draft design, (4) Initial draft validation and revision, (5) Product trial (small-scale trial/revision, large-scale trial/revision), (6) Final product, (7) Effectiveness test. The research subjects were ten volleyball extracurricular students at SMA Negeri 10 Purworejo Regency and ten students of SMK Vip Ma’arif Nu 1 Kemiri. The validation results showed that the developed training model was declared "valid" with a score of 0.825 from the material expert and 0.75 from the media expert’s score. Then the results of expert validation in small-scale trials got a score of 0.818 with the criteria of "valid", then for the results of expert validation in large-scale trials got a score of 0.85 with the criteria of "very high and valid". The effectiveness test got a p-value smaller than 0.05, namely 0.00 <0.05. These results indicate that the development of a drill smash training model using root obstacle media is effectively applied in extracurricular activities to improve smash accuracy in volleyball extracurricular students. These results indicate that there is an influence on the development of a straight and cross-direction drill smash training model using root obstacle media to improve smash accuracy in extracurricular volleyball students.